The use of heart rate variability in assessing precompetitive stress in high-standard judo athletes - Morales, J.; Garcia, V.; Garcia-Massó, X.; Salvá, P.; Escobar, R.; Buscà, B. (International Journal of Sports Medicine, 2013)
The objective of this study is to examine the sensitivity to and changes in heart rate variability (HRV) in stressful situations before judo competitions and to observe the differences among judo athletes according to their competitive standards in both official and unofficial competitions. 24 (10 male and 14 female) national- and international-standard athletes were evaluated. Each participant answered the Revised Competitive State Anxiety Inventory (CSAI-2R) and their HRV was recorded both during an official and unofficial competition. The MANOVA showed significant main effects of the athlete's standard and the type of competition in CSAI-2R, in HRV time domain, in HRV frequency domain and in HRV nonlinear analysis (p<0.05). International-standard judo athletes have lower somatic anxiety, cognitive anxiety, heart rate and low-high frequency ratio than national-standard athletes (p<0.05). International-standard athletes have a higher confidence, mean RR interval, standard deviation of RR, square root of the mean squared difference of successive RR intervals, number of consecutive RR that differ by more than 5 ms, short-term variability, long-term variability, long-range scaling exponents and short-range scaling exponent than national-standard judo athletes. In conclusion, international-standard athletes show less pre-competitive anxiety than the national-standard athletes and HRV analysis is sensitive to changes in pre-competitive anxiety.